2020
DOI: 10.3847/1538-4357/ab7816
|View full text |Cite
|
Sign up to set email alerts
|

Proper Motions of the Radio Source Orion MR, Formerly Known as Orion n, and New Sources with Large Proper Motions in Orion BN/KL

Abstract: The infrared source known as Orion n was detected in 1980 with observations made with the 3.8-m United Kingdom Infrared Telescope. About two decades later, sensitive observations made with the Very Large Array revealed the presence of a mJy double radio source apparently coincident in position with the infrared source n. The radio source was assumed to be the counterpart of the infrared source. However, over the years it has been concluded that the radio source shows large proper motions to the south while the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…The absolute PM of these sources are listed in Table 4 also indicating their equivalent transverse velocities for an adopted distance of 400 pc. The source SW1 (Zapata 11;Zapata et al 2004) was originally reported by Menten & Reid (1995) and its PM have been well constrained on longer timescales using up to 9 VLA epochs ranging from 1985 to 2018 (Dzib et al 2017;Rodríguez et al 2020) reporting PM consistent with our measurements. Additionally, Forbrich et al (2016) reported spectral index measurement for this source with negative value of −0.3±0.09 suggesting nonthermal emission, which has been actually found for YSO jets (see Section 6 in Anglada et al 2018 and reference therein).…”
Section: Proper Motionssupporting
confidence: 80%
See 2 more Smart Citations
“…The absolute PM of these sources are listed in Table 4 also indicating their equivalent transverse velocities for an adopted distance of 400 pc. The source SW1 (Zapata 11;Zapata et al 2004) was originally reported by Menten & Reid (1995) and its PM have been well constrained on longer timescales using up to 9 VLA epochs ranging from 1985 to 2018 (Dzib et al 2017;Rodríguez et al 2020) reporting PM consistent with our measurements. Additionally, Forbrich et al (2016) reported spectral index measurement for this source with negative value of −0.3±0.09 suggesting nonthermal emission, which has been actually found for YSO jets (see Section 6 in Anglada et al 2018 and reference therein).…”
Section: Proper Motionssupporting
confidence: 80%
“…Stars with velocities >10 km s −1 are considered peculiar sources and above 30 km s −1 are already in the runaway regime (Farias et al 2020;Schoettler et al 2020). Stellar proper motions in the ONC are typically 𝜇 𝑡𝑜𝑡 2 mas yr −1 (4 km s −1 ) (Dzib et al 2017;Kim et al 2019) and only a handful number of sources have fast proper motions with 𝜇 𝑡𝑜𝑡 30 mas yr −1 (60 km s −1 ) (Gómez et al 2005(Gómez et al , 2008Rodríguez et al 2020) most of them associated to the ejected stars in the BN/KL region (which will be discussed later in this section).…”
Section: Proper Motionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This differs from the NIR H 2 emission, part of which is absorbed by massive dust emission associated with the KL nebula (Johnstone & Bally 1999). The CO filaments and H 2 fingers can be traced back to a common origin (Zapata et al 2009;Bally et al 2011Bally et al , 2015Bally et al , 2017) that is consistent with the position to which the proper motions of various radio and NIR emitting young stellar projects can be traced back in space and time (Rodríguez et al 2005;Gómez et al 2005Gómez et al , 2008Luhman et al 2017;Rodríguez et al 2017;Bally et al 2020;Rodríguez et al 2020). Based on their Very Large Array (VLA) proper motion determinations, Rodríguez et al (2017) determine the year 1445 ± 6 as the time when the most prominent radio sources, Source I (in the following Src I) and the Becklin-Neugebauser object (BN), were closest together.…”
Section: Introduction 1the Energetics Of the Orion Kl Nebulamentioning
confidence: 67%
“…These findings constitute persuasive evidence the explosion resulted from the merger of young stellar objects, at least one of them massive (Src I), a scenario first discussed by Bally & Zinnecker (2005) in which the 10 48 -10 49 ergs injected into the region represent binding energy released by the orbital decay of components of a multiple system. More detailed observations suggest a more complex picture, a.o., suggesting ejections of sources at later times (Rodríguez et al 2020).…”
Section: Introduction 1the Energetics Of the Orion Kl Nebulamentioning
confidence: 98%